Qualidade de abóbora minimamente processada armazenada em atmosfera modificada ativa - Russo, Viviane Citadini [UNESP]; Daiuto, Érica Regina [UNESP]; Santos, Bruna Lourenco [UNESP]; Lozano, Mariana Goncalves [UNESP]; Vieites, Rogério Lopes [UNESP]; da Silva Vieira, Marcos Ribeiro (Universidade Estadual de Londrina (UEL), 2012)
The active modified atmosphere effect was evaluated in the quality of squash fresh-cut (MP).. The squash pieces were conditioned in plastic packings and submitted the gases application in the following concentrations: 0.03% CO2 and 21% O-2 (controls T1); 5% CO2 and 4% O-2 (T2); 6% CO2 and 4% O-2 (T3); 7% CO2 and 4% O-2 (T4); 8% CO2 and 4% O-2 (T5). In T6 it was made vacuum application in the packing. The packings containing the squash were stored in to the temperature of 10 degrees C and relative humidity of 75% for 12 days. The evaluated analyses were weigth loss, total acidity (AT), pH, soluble solids (SS), ratio, firmness, color, antioxidant activity for DPPH and carotenoids content. The weigth loss was gradual and low until the ninth day of storage. The values of AT increased along the experimental period being superior for T1 and T2. The increase of SS during the storage of the fresh-cut squash went smaller for T3 and T4. The brightness stayed during the storage being superior for T5, already the color components red and yellow decreased along the experimental period.
Quality of fresh-cut squash stored in active modified atmosphere
Keywords: Curcubita maxima Duchesne; antioxidant activity; carotenoids